Implementasi Analisis Keranjang Belanja Dengan Aturan Asosiasi Menggunakan Algoritma Apriori Pada Penjualan Suku Cadang Motor - Denny Haryanto; Yetli Oslan; Djoni Dwiyana (Universitas Atma Jaya Yogyakarta, 2011)
Abstract. Implementation of Shopping Cart Analysis with Assosiation Rules using Apriori Algorithm on Motorcycle Spare Parts Sales. At a distributor agent, most sales transactions are recorded in one information system. Data recorded, are only used for administrative purposes. Whereas these data contain information that can be processed for the other purposes. One is to find a special relationship between the products purchased at the same time. Based on these relationships, it is possible to do promotional items with bond patterns of the products. Consumers who buy the products will be interested to buy other products commonly bought. If consumers do not buy the products that exist in the pattern of sales of products, the distributor can offer products that exist in the pattern of sales of products. One of the combinations of pattern discovery algorithms products is apriori algorithm. The use of association methods in the search bond patterns of the products for the promotion of a product, is to minimize the promotion of products that have a low level of sales. By minimizing the promotional items that are not purchased, consumers will not interfere with the promotional items that do not have bond pattern, so that the promotional item will be more effective.Â Keywords: Apriori Algorithm, Assosiation Rules, Sales Promotion, Sales Transacation, Bond PatternÂ Abstrak. Pada agen distributor, kebanyakan transaksi penjualan dicatat dalam satu sistem informasi. Data hasil pencatatan hanya digunakan untuk keperluan administrasi. Padahal data tersebut mengandung informasi yang dapat diproses untuk keperluan yang lebih luas. Salah satunya adalah untuk menemukan hubungan khusus antar produk yang dibeli bersamaan. Berdasarkan hubungan tersebut, dimungkinkan melakukan promosi barang dengan pola keterikatan barang tersebut. Konsumen yang membeli barang akan tertarik untuk membeli barang yang lain yang biasa dibelinya. Bila konsumen tidak membeli barang yang ada dalam pola penjualan barang, distributor dapat menawarkan barang yang ada dalam pola penjualan barang. Salah satu algoritma penemuan kombinasi pola barang adalah algoritma apriori. Penggunaan metode asosiasi dalam pencarian pola keterikatan untuk promosi produk, diharapkan dapat meminimalkan promosi barang yang mempunyai tingkat penjualan rendah. Dengan meminimalkan promosi barang yang tidak terbeli, konsumen tidak akan terganggu dengan promosi barang yang tidak mempunyai pola keterikatan, sehingga promosi akan lebih efektif.Â Kata Kunci: Algioritma Apriori, Aturan Asosiasi, Promosi Penjualan, Transaksi Penjualan, Pola Keterikatan